The nexus between financial sector consolidation, competition and efficiency: empirical evidence from the Malaysian banking sector - Sufian, Fadzlan (Oxford University Press, 2011)
By employing data on 337 bank-year observations, the paper examines the impact of consolidation on efficiency and competition in the Malaysian banking sector during 1996–2008. We employ the Panzar-Rosse (P-R) H-statistic method to evaluate the degree of competition, while Data Envelopment Analysis (DEA) is employed to compute the efficiency of individual banks. The empirical findings from the DEA suggest that the Malaysian banking sector has been relatively inefficient in their intermediation function during the post-merger period. On the other hand, we find that the Malaysian banking sector has been relatively more efficient during the post-merger period under the revenue approach. The test of market contestability by using the P-R method seems to reject both monopoly and perfect market competition conditions indicating monopolistic market behaviours among banks operating in the Malaysian banking sector.